Marxist theory of land rent : original exposure and contemporary reformulations (2015)
Here is presented an English version of the first two chapters of the book of Samuel Jaramillo Hacia una teoría de la renta del suelo urbano (2009) (Towards a theory of Urban Land Rent) that is only published in Spanish. This is justified because the theme developed in these two chapters have greater thematic scope than the book, since it refers to the general category of rent, which has a crucial role in the Marxist interpretation of value and price formation in capitalism, and these days it is the subject of several debates. Therefore, it may be interesting not only to those involved in real estate and urban phenomena. The two chapters have autonomy and great consistency as text. Its approach is original and challenging, as shown by the discussions awakened by the Spanish version. With this publication we want to broaden the spectrum of these theses and introduce them to those who do not speak Spanish and are interested in the topic of land property...